Firms' performance and risk with the presence of Sukuk rating as default risk / Nurul Hidayah Ab Hamid - Ab Hamid, Nurul Hidayah (2012)
This research aims to examine the role income stream risk, stock return risk, strategic risk and default risk in explaining corporate performance. Approximately as much 312 from 2008 until 2011 listed firms are chosen a cross industries in Malaysia to represent the sample firms. The Sukuk rating emerge as surrogate for default risk, the corporate performance indicators are based on the return on assets and return on equity. The contribution of the research result may leads on introducing the default risk measures by Sukuk based on the uniqueness of Malaysian data in applying the Shariah compliance.